Rare lymphomas in routine practice – Treatment and outcome in marginal zone lymphoma in the prospective German Tumour Registry Lymphatic Neoplasms. Issue 3 (4th May 2021) - Knauf, Wolfgang; Abenhardt, Wolfgang; Koenigsmann, Michael; Maintz, Christoph; Sandner, Reiner; Zahn, Mark‐Oliver; Schnell, Roland; Tech, Susanne; Kaiser‐Osterhues, Anja; Houet, Leonora; Marschner, Norbert; ,
Abstract: Owing to its heterogeneity and rarity, management of disseminated marginal zone B‐cell lymphoma (MZL) remains largely understudied. We present prospective data on choice of systemic treatment and survival of patients with MZL treated in German routine practice. Of 175 patients with MZL who had been documented in the prospective clinical cohort study Tumour Registry Lymphatic Neoplasms (NCT00889798) collecting data on systemic treatment, 58 were classified as extranodal MZL of mucosa‐associated lymphoid tissue (MALT) and 117 as non‐MALT MZL. We analyzed the most commonly used first‐line and second‐line chemo(immuno)therapies between 2009 and 2016 and examined objective response rate (ORR), progression‐free survival (PFS), overall survival (OS) and prognostic factors for survival. Compared to patients with MALT MZL, those with non‐MALT MZL more often presented with bone marrow involvement (43% vs. 14%), Ann Arbor stage III/IV (72% vs. 57%) and were slightly less often in good general condition (ECOG = 0; 41% vs. 47%). In German routine practice, rituximab‐bendamustine for a median of 6 cycles was the most frequently used first‐line (76%) and second‐line treatment (36%), with no major differences between MZL subtypes. The ORR for patients encompassing any positive response was 81%. For patients with MALT and non‐MALT MZL, respectively, 5‐years PFS was 69% (95% CI 52%–81%) and 66% (95% CI 56%–75%), 5‐years OS 79% (95% CI 65%–89%) and 75% (95% CI 66%–83%). Cox proportional hazards models showed a significantly increased risk of mortality for higher age in all patient groups. Our prospective real world data give valuable insights into the management and outcome of non‐selected patients with MZL requiring systemic treatment and can help optimize therapy recommendations.